2023
DOI: 10.1021/acs.jpcc.3c00467
|View full text |Cite
|
Sign up to set email alerts
|

Far-Field Polarization Optics Control the Nanometer-Scale Pattern of High-Fluorescence Dissymmetry Emission from Achiral Molecules near Plasmonic Nanodimers

Abstract: Chiroptical spectroscopies like circular dichroism report on the handedness of molecules but are often limited to the high-concentration regime because of the mismatch between the wavelength of propagating visible light and the size of molecules. Recent work has demonstrated that the electromagnetic fields generated near chiral plasmonic nanostructures can have high optical chirality that bridges these length scales and can induce high-fluorescence dissymmetry signals from achiral dyes by redirecting their emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…7−9 Fibril chirality can be measured with circular dichroism. 10 This measurement typically requires high concentrations (∼100 μM) and sufficiently large volumes (∼1 mL) for a sufficient enough signal. A recent study has also shown that plasmonic nanoparticles that match the fibril pitch form ordered structures around the fibril, which can be used to detect fibril chirality at low concentrations.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…7−9 Fibril chirality can be measured with circular dichroism. 10 This measurement typically requires high concentrations (∼100 μM) and sufficiently large volumes (∼1 mL) for a sufficient enough signal. A recent study has also shown that plasmonic nanoparticles that match the fibril pitch form ordered structures around the fibril, which can be used to detect fibril chirality at low concentrations.…”
mentioning
confidence: 99%
“…We designed single-particle fluorescence polarimetry experiments to distinguish between these mechanisms by measuring if there is a significant chiroptical response when a single AuNR is coupled to fibrils and proximal to fibril-bound ThT molecules. 10 The experiments were also designed to investigate the heterogeneity in the circular differential absorption of single particles, a distribution that is hidden in the ensemble measurement (Figure 1a). We find monomeric AuNRs have no detectable induced circular dichroism (CD) signal, and thus, the net CD signal cannot be attributed to the sum of the induced CD from monomeric AuNRs.…”
mentioning
confidence: 99%
See 3 more Smart Citations